2003
DOI: 10.1590/s0036-46652003000300006
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of congenital toxoplasmosis in southern Brazil: a prospective study

Abstract: SUMMARYThe study aimed to determine the incidence of congenital infection by Toxoplasma gondii and to describe neonatal and maternal characteristics regarding newborn infants treated at a teaching hospital in the town of Passo Fundo, State of Rio Grande do Sul, Brazil. Cord blood samples collected from 1,250 live newborns were analyzed. The laboratory diagnosis was established by the detection of Toxoplasma gondii IgM using an enzyme linked fluorescent assay. Gestational age, intrauterine growth, anthropometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
9

Year Published

2005
2005
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 17 publications
2
19
0
9
Order By: Relevance
“…The prevalence of CTox by the end of the first year of life in our study (0.9/1,000 newborns) was comparable to that found at birth in other areas of Southern Brazil (Glasner et al 1992, Mozzatto & Procianoy 2003, Lago et al 2007. A prevalence of 5.0/1,000 newborns reported in Minas Gerais, Brazil, could partially be explained by the use of cord blood samples (Segundo et al 2004).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The prevalence of CTox by the end of the first year of life in our study (0.9/1,000 newborns) was comparable to that found at birth in other areas of Southern Brazil (Glasner et al 1992, Mozzatto & Procianoy 2003, Lago et al 2007. A prevalence of 5.0/1,000 newborns reported in Minas Gerais, Brazil, could partially be explained by the use of cord blood samples (Segundo et al 2004).…”
Section: Discussionsupporting
confidence: 84%
“…In the Southern region, the prevalence of congenital infection based on cord blood samples reached 0.8/1,000 births (95% CI: 0.02-4.45) (Mozzatto & Procianoy 2003). Other studies using blood samples adsorbed onto filter paper found prevalences from 0.3/1,000 (Neto et al 2000) to 0.6/1,000 newborns (Lago et al 2007).…”
mentioning
confidence: 94%
“…Previous studies show that this region has a high prevalence of ocular acquired toxoplasmosis, and concomitantly, the rate of congenital toxoplasmosis currently can be considered as one of the highest in the world. [2][3][4]32,33 It has been widely accepted that approximately 90% of newborns with a serological diagnosis of congenital toxoplasmosis have a normal physical examination at birth and only about 40% present ocular and/or neurological alterations after further investigation. 6,15,18 This study definitely showed that ocular involvement may be more frequent and occurs earlier than previously described.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies conducted in Rio Grande do Sul, Brazil, a high incidence of congenital toxoplasmosis was shown, ranging from 6 to 8 per 10 000 live births. [2][3][4] Vertical transmission of toxoplasmosis occurs during primary infection in pregnant women, and generally the maternal disease goes unnoticed. When pregnant women become infected in the first trimester, the frequency of fetal infection goes up to 15-20%, in the second up to 25%, and in the third up to 65-70%.…”
Section: Introductionmentioning
confidence: 99%
“…Os casos de reativação da infecção pelo T. gondii, causados por imunossupressão materna, poderiam levar à infecção do feto durante a gravidez (52) . O sucesso da infecção fetal depende de fatores como virulência do T. gondii, desenvolvimento placentário, idade gestacional e carga parasitária, entre outros (1) .…”
Section: Introductionunclassified